A Case of Hyperacute Severe Thrombocytopenia Occurring Less than 24 Hours after Intravenous Tirofiban Infusion - Vineet Meghrajani; Nitin Sabharwal; Vinod Namana; Moustafa Elsheshtawy; Bernard Topi (Case Reports in Hematology)
Thrombocytopenia is defined as a condition where the platelet count is below the lower limit of normal (<150 G/L), and it is categorized as mild (100–149 G/L), moderate (50–99 G/L), and severe (<50 G/L). We present here a 79-year-old man who developed severe thrombocytopenia with a platelet count of 6 G/L, less than 24 hours after intravenous tirofiban infusion that was given to the patient during a percutaneous transluminal coronary angioplasty procedure with placement of 3 drug-eluting stents. The patient’s baseline platelet count was 233 G/L before the procedure. Based on the timeline of events during hospitalization and laboratory evidence, it was highly likely that the patient’s thrombocytopenia was the result of tirofiban-induced immune thrombocytopenia, a type of drug-induced immune thrombocytopenia (DITP) which occurs due to drug-dependent antibody-mediated platelet destruction. Anticoagulant-mediated artefactual pseudothrombocytopenia was ruled out as no platelet clumping was seen on the peripheral blood smears. The treatment of DITP includes discontinuation of the causative drug; monitoring of platelet count recovery; or treatment of severe thrombocytopenia with glucocorticoids, IVIG, or platelet transfusions depending on the clinical presentation. The most likely causative agent of this patient’s thrombocytopenia—tirofiban—was discontinued, and the patient did not develop any signs of bleeding during the remainder of his hospital stay. His platelet count gradually improved to 24 G/L, and he was discharged on the sixth hospital day.